Analytical and Biological Evaluation of Chromium Complex with Organic Detector NTADBrP: Stability, Calibration, and Inhibition Studies - Mustafa Subhi Fattah; Shaimaa Mohsen Essa (Engineering Proceedings)
This study provides a comprehensive investigation into the formation, characteristics, and biological activity of a chromium complex with the organic reagent NTADBrP. The article presents detailed insights into the H1-NMR spectrum of the organic reagent and examines the optimal conditions for chromium complex formation, considering the effects of time, pH, and temperature. The stoichiometry and stability constant of the complex are determined using specific methods, leading to the calculation of a significant stability constant. Additionally, a calibration curve for the chromium ion is derived, and the complex’s biological activity against Escherichia coli and Staphylococcus bacteria is studied. These findings contribute to the understanding of chromium complex behavior and open new avenues for applications in analytical chemistry and pharmaceutical research.